An Analysis Of Inpatient Satisfaction At Maria Walanda Maramis Regional General Hospital - Venesia Pengan; Jehosua S. V. Sinolungan; Jimmy Posangi; Dina V. Rombot; Markus T. Lasut; Welong S. Surya (International Journal of Health and Pharmaceutical (IJHP), 2025)
Patient satisfaction serves as a critical indicator of hospital service quality and overall performance. In Indonesia, government hospitals are required to adhere to public service standards, including routine evaluation through the Community Satisfaction Index (IKM). This study examines patient satisfaction among inpatients at RSUD Maria Walanda Maramis, North Minahasa, using four core service quality dimensions: system and procedure clarity, service completion time, staff competence, and infrastructure. To analyze the relationship between selected service quality variables and the level of patient satisfaction in a Type C public hospital. Methods: This research employed a quantitative, cross-sectional design involving 95 inpatients selected using simple random sampling. Data were collected via a structured questionnaire adapted from Permenpan RB No. 14/2017. Bivariate analysis using the Chi-square test was conducted to determine the significance of associations, and Odds Ratios (OR) were calculated to measure the strength of influence of each variable on satisfaction. Results: All four independent variables showed significant associations with patient satisfaction (p < 0.05). The strongest influence was found in the clarity of service systems and procedures (OR = 14.0), followed by infrastructure (OR = 4.219), staff competence (OR = 3.889), and turnaround time (OR = 3.372). Infrastructure received the highest percentage of positive responses (72.6%), while staff competence received the lowest (51.6%). Conclusion: Patient satisfaction at RSUD Maria Walanda Maramis is significantly influenced by administrative clarity, service efficiency, human resource competence, and facility quality. Enhancing procedural transparency and investing in continuous staff development are crucial strategies for improving hospital service quality and public perception.